An improvement of defected ground structure lowpass/bandpass filters using H-slot resonators and coupling matrix method - Ahmed Boutejdar; Abbas Omar; Edmund P. Burte; Reinhard Mikuta (Journal of Microwaves, Optoelectronics and Electromagnetic Applications)
A novel compact wideband high-rejection lowpass filter (LPF) using H-DGS is presented. The proposed filter has neither open stub nor cascaded high-low impedance elements. It consists of two coupled H-slots in the ground plane along with a compensated line. The effect of the new slot on the filter performance is examined. The comparison with the conventional filters shows that the proposed one guarantees a large rejected-band of 20dB from 2.5 to 16 GHz. Experimental measurements by means of HP8719D network analyzer agree well with simulated results which are carried out by Microwave Office. Based on H-DGS LPF Structure, a novel bandpass filter (BPF) will be is designed and tested verified by using both J-inverter and coupling matrix methods.